Natural History of Gastric Mucosal Cytokine Expression in Helicobacter pylori Gastritis in Mongolian Gerbils - Yamaoka, Yoshio (American Society for Microbiology, 2005)
Data regarding the chronological changes in gastric mucosal cytokines in the different phases of Helicobacter pylori infection are unavailable. We examined Mongolian gerbils for up to 52 weeks after H. pylori (ATCC 43504) inoculation. Levels of mRNAs of mucosal cytokines (interleukin-1β [IL-1β], gamma interferon [IFN-γ], IL-4, IL-6, and IL-10) were assessed using real-time reverse transcription-PCR. Starting 26 weeks after H. pylori inoculation, two clinicohistologic patterns appeared: gastric ulcers in 32% and hyperplastic polyps in 68% of gerbils. High levels of mucosal IL-1β mRNA were observed early in the infection, reaching maximum at 4 weeks and then rapidly declining. Mucosal IFN-γ mRNA also reached maximal levels at 4 weeks but remained high thereafter. Both IL-1β and IFN-γ mRNA levels were consistently higher in the pyloric mucosa than in the fundic mucosa. In contrast, IL-4, IL-6, and IL-10 mRNA levels peaked at 8 to 26 weeks and levels were similar in the pyloric mucosa and the fundic mucosa. IFN-γ mRNA levels were significantly higher in gerbils with ulcers than in those with hyperplastic polyps (median IFN-γ/glyceraldehyde-3-phosphate dehydrogenase ratio × 100,000 = 650 versus 338, respectively [antrum], and 172 versus 40, respectively [corpus]) (P < 0.05). We propose that the different outcomes (e.g., ulcers or hyperplastic polyps) might relate to imbalances among cytokines.